Regional Patterns and Determinants of the Success of New Firms in Western Germany - Reinhold Grotz; Udo Brixy (European Regional Science Association (ERSA), 2003)
There exists a large body of literature on the determinants of regional variation in new firm formation. In contrast there are only a few articles on the spatial differences of new firm survival. Using panel data we analyse both items for 74 West-German regions of a ten years period. Our aim is to focus on the relationship of both rates. It seems convincing that regions with high birth-rates should also have high survival-rates, because a favourable environment for the founding of new firms should also be encouraging for the development of these firms. But already a descriptive analysis of both rates reveals the existence of a negative relationship in general. This means that in regions with high birth-rates the survival rates are lower than the average. But despite this correlation in general it is shown that the spatial pattern of a combination of both rates is complex and there exist all types of possible relationships. With a multivariate panel analysis we study the factors that influence regional birth-rates and survival-rates in a similar way, that means with the same method and the same set of independent variables. It is shown that in the service sector most variables are literally working in opposite direction in birth-rates and survival-rates models. But this holds not for the producing industry. Here, the above mentioned thesis is true. The reason for this is a complete different outcome of the estimated birth-rates models for both industry-sectors, whereas there are only minor differences in the estimated survival-rate-models. We can deduce therefore, first that both industries have different requirements of their “seed bed” but not for their further successful development. Second, that the spatial structures that increase the number of newly founded businesses in the service sector are adverse to the survival-rates of newly founded firms.
Keywords: 330